The Influence of Motivation, Work Discipline and Work Environment on The Performance of Employees of The Labor and Trade Industry Office of XYZ City - R. Rudi Alhempi; Utami Wahyuningsih; Suharto Ngudiwaluyo; Sahlan Sahlan (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This study aims to examine the effect of motivation, work discipline, and work environment on the performance of civil servants in the agency. Data collection was carried out using the questionnaire method. The research data was analyzed quantitatively using multiple linear regression method with the help of SPSS 24.0 application. The results of quantitative analysis show that motivation, work discipline, and work environment have a positive and significant effect on the performance of employees of the XYZ City Trade and Manpower and Industry Office, both partially and simultaneously. Where partially with the t test shows that motivation has a tcount of 3.904 with a significant value of 0.000, work discipline has a tcount of 2.853 with a significance of 0.007, and the work environment has a tcount of 3.383 with a significant value of 0.002 so that the most dominant variable affecting employee performance is the work environment variable with the largest tcal. While simultaneously with the F test shows that the resulting Fcalculate is 212.105 with a significant value of 0.000. The results of the determination test show that 93.1% of employee performance can be explained and obtained from motivation, work discipline, and work environment, while the rest is obtained from other factors. Where employee performance has a very strong relationship to motivation, work discipline, and work environment.